1999
DOI: 10.1002/(sici)1521-396x(199903)172:1<183::aid-pssa183>3.3.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Stimulated Conductivity and Luminescence in Polycrystalline Diamond Films

Abstract: Thermally stimulated currents (TSC) and thermoluminescence (TL) have been studied in polycrystalline diamond films of different qualities in order to gain information about the deep levels present within the bandgap of this material. The TL has been studied between 300 and 670 K after UV light illumination, and the TSC between 300 and 600 K after various excitations (UV light, from a tungsten lamp, X-rays). TL and TSC peaks are observed at 470 and 560 K, and depend on the quality of the diamond and on the illu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…Similar evidence has been reported in Ref. 34, where a peak at 450 K with a corresponding cross section of Ϸ10 Ϫ19 cm 2 was observed by TSC with ␤ϭ0.2 K/s. Vittone et al 29 found by TL analysis ͑␤ϭ8 K/s͒ evidence for at least two deep levels in the range E t ϭ0.98-1.12 eV, Ϸ10 Ϫ18 -10 Ϫ19 cm 2 .…”
Section: A Deep Level Contentsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar evidence has been reported in Ref. 34, where a peak at 450 K with a corresponding cross section of Ϸ10 Ϫ19 cm 2 was observed by TSC with ␤ϭ0.2 K/s. Vittone et al 29 found by TL analysis ͑␤ϭ8 K/s͒ evidence for at least two deep levels in the range E t ϭ0.98-1.12 eV, Ϸ10 Ϫ18 -10 Ϫ19 cm 2 .…”
Section: A Deep Level Contentsupporting
confidence: 90%
“…29 In the many studies found in the literature, one or more of these thermal spectroscopy techniques has been used in the investigation of boron-doped CVD diamond, [30][31][32] and undoped CVD diamond. 18,[25][26][27][28][29][30][31][32][33][34][35][36][37] In some of these works, the capture cross section has been calculated explicitly, while in other cases it can be deduced either from the activation energy and the glow curve peak position, or from the TL frequency factor s. However, in general, values of deduced solely from a single experimental technique have a large systematic uncertainty, because spectra are composed of many overlapping deep level contributions, and thus can be explained by different sets of pairs of parameters (E t ,).…”
Section: Introductionmentioning
confidence: 99%
“…Diamond in the form of CVD films possess extraordinary properties: high radiation resistance, tissue equivalency, chemically stability and non-toxicity, that may place diamond as perhaps the most promising TLD/OSLD material of the future. Although, the TL performance of CVD diamond are quite well investigated for α, β, γ and even protons [3 -6] as well as UV radiation [7][8][9] with great expectative in medical applications [10], that is not the case for OSL. Since boron is known to improve the TL efficiency of CVD diamond film as compared to non doped diamond, it was expected to find an enhanced OSL intensity output in B/C-doped CVD diamond.…”
Section: Introductionmentioning
confidence: 99%